Preparing the U.S. Army for homeland security : concepts, issues, and options - Larson, Eric V. (Eric Victor), 1957-; Peters, John E., 1947- (MR (Series), 2001)
Homeland security encompasses five distinct missions: domestic preparedness and civil support in case of attacks on civilians, continuity of government, continuity of military operations, border and coastal defense, and national missile defense. This report extensively details four of those mission areas (national missile defense having been covered in great detail elsewhere). The authors define homeland security and its mission areas, provide a methodology for assessing homeland security response options, and review relevant trend data for each mission area. They also assess the adequacy of the doctrine, organizations, training, leadership, materiel, and soldier systems and provide illustrative scenarios to help clarify Army planning priorities. The report concludes with options and recommendations for developing more cost-effective programs and recommends a planning framework that can facilitate planning to meet homeland security needs.